PELATIHAN PENGGUNAAN TABLE OF FIGURES (TOF) DAN INSERT CAPTION UNTUK MEMBUAT DAFTAR TABEL DAN DAFTAR GAMBAR MAKALAH SECARA OTOMATIS DI SMK PAB 8 SAMPALI - Elida Tuti Siregar; Ommi Alfina; Suci Rahmadani (Universitas Methodist Indonesia, 2021)
The purpose of community service activities is to implement the Tri Dharma of Higher Education and provide learning how to use Table of Figures (TOF) and Insert Captions to create a list of tables and a list of pictures of papers automatically at SMK PAB 8 Sampali. A paper is a work that is written, has a scientific nature and contains a discussion on a particular topic. In a paper, a table of contents, a list of tables and a table of figures is one of the components that must be present. Generally, students often make lists of tables and lists of pictures manually. As a result, sometimes the results obtained are not neat and not in accordance with the rules of writing the correct picture list. Even though Microsoft Word has provided the Insert Table of Figures feature that makes it easy for users to create a list of images or a list of tables automatically. Through training for SMK PAB 8 Sampali students, it is hoped that they will be able to use Table of Figures (TOF) and Insert Captions to write papers correctly as a support in the teaching and learning process.